An Analysis of VIII Grade Students' Science Literacy Skills in Junior High School in PadangAnalysis of VIII Grade Students' Science Literacy Skills in Junior High School in Padang - Devinda, Devinda; Violita, Violita (Literasi Bahasa dan Sastra Jurnal, 2024)
Purpose of the research was to describe the result of VIII Grade Students' Science Literacy Skills analysis in Junior High School in Padang. It was a descriptive research. Samples were taken by using purposive sampling technique. Techniques of data collection used valid and reliable science literacy test and interview with students and teachers. Technique of data analysis was by calculating average score of students' science literacy test. To test data validity, it used triangulation technique. The finding shows that VIII grade students' science literacy skill in SMPN 1 Padang based on total score, basic competence and science competence has the highest average score with low category. Then, it is followed by VIII grade students' science literacy skill in SMPN Ar-risalah Padang and SMP Manjushri Padang with low category. In conclusion, VIII grade students' science literacy skill in Junior High School in Padang is in low category.